Environmental toxicology - Wright, David A., 1948- (Cambridge environmental chemistry series, 2002)
Environmental Toxicology is a comprehensive introductory textbook dealing with all aspects of the subject. It is primarily a text for students in environmental toxicology, environmental chemistry, ecotoxicology, applied ecology, environmental management, and risk assessment. It will also be valuable for specialists in ecology, environmental science, and chemistry.